Methods for anti‐factor VIII antibody levels in haemophilia A patients – validation of a multiplex immunoassay and comparability with assays measuring non‐neutralising and neutralising antibodies (inhibitors). Issue 1 (3rd October 2022) - Martin, Myriam; Augustsson, Cecilia; Lind, Vivian; Al‐Sabti, Riam; Lam, My Chi; Andersson, Nadine G.; Strandberg, Karin
Abstract: Introduction: The development of neutralising (inhibitors) and non‐neutralising antibodies (NNAs) is a complication to factor replacement therapy in haemophilia. The diagnostic methods available lack standardisation, have high inter‐laboratory variation, and false‐negative as well as false‐positive results may affect treatment. Both functional inhibitors and NNAs may be detected with higher reproducibility, sensitivity and specificity using the immunological Luminex xMAP‐based fluorescence‐immunoassay (xFLI). Aim: Validation of our xFLI and comparability with enzyme‐linked immunosorbent assay (ELISA) and chromogenic Nijmegen‐Bethesda assay (CBA) for anti‐FVIII antibodies in haemophilia A (HA) patients. Methods: The xFLI method was developed with full‐length and B‐domain deleted factor coupled to magnetic beads, optimised and validated for performance characteristics. Comparability with ELISA and CBA was evaluated in HA patient samples ( n  = 112), serial samples in six inhibitor patients and reference interval and decision‐limits in healthy donors ( n  = 44). Results: The intra‐ and inter‐assay precision (CV%) for the xFLI method was below 6% and detection limit (LLOQ) .084 ng/mL (NovoEight). All ELISA‐positive samples were positive with either Advate or NovoEight. Additionally, 10.7%–14.3% were xFLI‐positive and ELISA‐negative. All but one CBA‐positive sample was above 3SD with xFLI; one was between 2 and 3SD. 29.1% were xFLI‐positive and CBA negative. The overall concordance between xFLI and ELISA was 82.1% and xFLI and CBA 77.9%. Conclusion: The anti‐FVIII antibody xFLI method is adaptable to clinical practice and more sensitive and reproducible than ELISA and CBA. Actual NNA titers are determined to both full‐length and B‐domain deleted FVIII. The xFLI is thus valuable for confirmation of all anti‐FVIII antibodies.